Localized surface plasmon resonance enhanced photocurrent with gold nanoparticles coated on FTO - Lam, Kian Yong (2013)
Gold nanoparticles were coated on FTO glasses using electroplating method to induce localized surface plasmon resonance effect to enhance light harvesting and photocurrent for dye sensitized solar cell (DSSC). Step time of electroplating is varied for each device while applied voltage is kept at constant of -0.5v. Results revealed that devices coated with gold nanoparticles showed an improvement of short circuit current, with an average factor of 2.48% while open circuit voltage does not experience large variation. 5s device showed an enhancement of nearly 54% of induced photon to photocurrent efficiency (IPCE) at peak spectral of 520nm because the maximum absorption of gold nanoparticles occur at 520nm-570nm. SEM image illustrated that increase step time of electroplating increase the distribution of gold nanoparticles on the electrode. This approach is useful in enhancing the efficiency of DSSC while minimizing the thickness of TiO2 layer.